Identification of differentially expressed genes during somatic embryogenesis of Axonopus compressus by restriction fragment differential display-coupled FSD - See, Pao Theen; Abdul Rahman, Siti Suhaila; Chin, Chiew Foan; Kulaveerasingam, Harikrishna (Malaysian Society for Molecular Biology and Biotechnology, 2003)
We present an approach to profile the expression of gene family members during somatic embryogenesis of Axonopus compressus through the modification of a recently developed RNA fingerprinting method. The protocol combines restriction fragment differential display technology with primers directed to a gene family specific domain signature on mRNA and hence is termed ‘RFDD-coupled FSD’. By using this method, two differentially expressed mRNAs, AC1 and AC2, containing the chromo-like domain and the serine/threonine protein kinase signatures, respectively, were isolated. Sequence analysis revealed that AC1encoded a MIP (plasma membrane protein) meanwhile AC2 shared low homology to other serine/threonine protein kinases. The abundance of these two transcripts appeared to be down-regulated in the embryogenic and non-viable embryogenic tissues when examined on Northern and semi-quantitative RT-PCR analyses, suggesting possible developmental arrest. This preliminary differential expression examination has somewhat provided a first insight into the molecular events underlying A. compressus somatic embryo development. Thus, RFDD-coupled FSD has been shown to be an efficient procedure for identifying differential regulated transcripts that correspond to their defined gene family domain signature sequences.